Procyanidin C1 Modulates the Microbiome to Increase FOXO1 Signaling and Valeric Acid Levels to Protect the Mucosal Barrier in Inflammatory Bowel Disease - Wang, Xifan; Wang, Pengjie; Li, Yixuan; Guo, Huiyuan; Wang, Ran; Liu, Siyuan; Qiu, Ju; Wang, Xiaoyu; Hao, Yanling; Zhao, Yunyi; Liao, Haiping; Zou, Zhongju; et al. (Engineering (Beijing, China), 2024)
Inflammatory bowel disease (IBD) refers to a pair of prevalent conditions (Crohn’s disease and ulcerative colitis) distinguished by persistent inflammation of the large intestine. Procyanidin C1 (PCC1) is a naturally occurring substance derived from grape seeds that has demonstrated notable anti-inflammatory properties. This study examines the potential utility of PCC1 as a treatment for IBD and subsequently examines the host-cell- and microbiome-related mechanisms underlying the detected therapeutic benefits. Working with a classic dextran sodium sulfate (DSS)-induced mouse IBD model, we show that PCC1 protects the mucosal barrier and thereby confers strong protective effects against IBD. PCC1 pretreatment resulted in anti-inflammatory effects and protection against multiple pathological phenotypes in the IBD model mice, including reduced weight loss, lower disease activity index (DAI) totals, and enhanced colon size, as well as obviously beneficial effects on the mucosal barrier (e.g., barrier thickness and activity of mucus-degrading enzymes). We also analyzed the autophagy marker microtubule- associated protein1 light chain 3 (LC3) and found that the level of LC3 was significantly elevated in the intestinal epithelial cell samples of the PCC1-pretreatment group as compared with the non-model mice samples. PCC1 altered the fecal microbiome composition, which included elevating the abundance of Akkermansia muciniphila and Christensenella minuta. Fecal microbiome transplant (FMT) experiments showed that delivering a microbiome from PCC1-treated animals into PCC1-naïve animals conferred protection. Metabolic profiling revealed that both the PCC1-pretreatment and PCC1 FMT groups had elevated levels of the microbiota-derived metabolite valeric acid, and supplementation with this short-chain fatty acid (SCFA) also conferred strong protection against IBD. Finally, inhibitor experiments confirmed that the beneficial effects of valeric acid on the mucus layer are mediated by FOXO1 signaling in the goblet cells of the intestinal epithelium. Beyond showing that PCC1 confers anti-inflammatory effects and protection against IBD by altering the microbiome, our study demonstrates proof of principle for multiple straightforward interventions (PCC1, FMT, and valeric acid supplementation) for ameliorating mucosal barrier damage to treat IBD.